Asset Pricing with a Reference Level of Consumption: New Evidence from the Cross-Section of Stock Returns - Andreas Schrimpf; Joachim G. Grammig (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
This paper presents an empirical evaluation of recently proposed asset pricing models which extend the standard preference specification by a reference level of consumption. We motivate an alternative model that accounts for the return on human capital as a determinant of the reference level. Our analysis is based on a broad cross-section of test assets which provides a level playing field for a comparison to established benchmark models. The human capital extended reference level model does a good job in explaining size and value premia. Estimated on Fama and French's size and book-to-market sorted portfolios it outperforms Lettau and Ludvigson's scaled CCAPM and delivers average pricing errors comparable to the Fama-French three-factor model.
Older version: http://hdl.handle.net/10419/24224
Keywords: G12; 330; Consumption-Based Asset Pricing; Cross-Section of Stock Returns; Reference Level; Börsenkurs; Kapitalertrag; Capital Asset Pricing Model; Schätzung; Theorie; Welt